Accessibility to Andrology Medical Devices in Arab-Muslim Countries - Mounir Jamali (Société Internationale d’Urologie Journal, 2024)
Highlighting the restricted access to andrology medical devices in Arab Muslim countries, where unjust associations with sexual instruments lead to prohibitions, this commentary underscores the challenges in providing appropriate medical care for andrological conditions. Despite the crucial role of devices like penile extenders, vacuum devices, and vibrators in treating conditions such as Peyronie’s disease and erectile dysfunction, cultural and religious biases condemn them in certain regions. This lack of understanding deprives many patients of andrological treatments, limiting therapeutic options and equitable healthcare access. The commentary advocates for urology societies to raise awareness, engage policymakers, and use media to distinguish these devices from sex toys, emphasizing their medical nature for the benefit of patients.